GLOBALIZATION PROCESS AND NATIONAL-SPIRITUAL FACTORS - Panjiev Suhrob (Galaxy International Interdisciplinary Research Journal, 2022)
The article expresses an opinion on problems such as analyzing the features of spiritual development and spiritual renewal in society in the process of globalization and learning ways to use the results of spiritual growth.